2019
DOI: 10.7150/ijbs.33233
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Micro RNAs Derived from Dermal Papilla Cells Mediate Hair Follicle Stem Cell Proliferation and Differentiation

Abstract: Recent studies have demonstrated that dermal papilla cell-derived exosomes (DPC-Exos) promote the anagen stage of hair follicle (HF) growth and delay the catagen stage. However, the roles of DPC-Exos in regulating hair follicle stem cell (HFSC) quiescence and activation remain unknown. Here, we found that HFSC differentiation was induced by co-culture with DPCs, and that DPC-Exos attached to the surface of HFSCs. Using micro RNA (miRNA) high-throughput sequencing, we identified 111 miRNAs that were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 76 publications
2
67
0
Order By: Relevance
“…The SHF stem cells of passage 3 of cashmere goat were utilized for the overexpression/siRNA interference analysis of circRNA-1926. The SHF stem cells were co-cultured with dermal papilla cells (DPCs) for inducing their differentiation into hair follicles lineage, which was performed in transwell devices as described by Yan and colleagues [18]. In brief, the SHF stem cells of passage 3 were plated on six-well plates, and then, a transwell insert was added in which passage 3 DPCs of cashmere goat was seeded.…”
Section: Cell Cultivation and Overexpression/sirna Interference Analymentioning
confidence: 99%
“…The SHF stem cells of passage 3 of cashmere goat were utilized for the overexpression/siRNA interference analysis of circRNA-1926. The SHF stem cells were co-cultured with dermal papilla cells (DPCs) for inducing their differentiation into hair follicles lineage, which was performed in transwell devices as described by Yan and colleagues [18]. In brief, the SHF stem cells of passage 3 were plated on six-well plates, and then, a transwell insert was added in which passage 3 DPCs of cashmere goat was seeded.…”
Section: Cell Cultivation and Overexpression/sirna Interference Analymentioning
confidence: 99%
“…In a recent work, Dai et al showed that thymosin β4, a screened gene from a transcriptomic analysis, is potentially capable of enhancing cashmere production through stimulating DPCs' proliferation [14]. Likewise, the suppressive role of miR-22-5p on HFSCs' expansion was also revealed, exhibiting that relieving this inhibitive effect may be an alternative for goat fiber enhancement [15]. Whereas, there are still few reports focusing on the in vitro propagations of goat HMCs, even widespread applications (e.g., exploring the mechanisms of male baldness and detecting the dynamic expression of wool keratins) have emerged for humans [16,17] and sheep [18].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of DPCs is an important source for the supplementation and growth of other hair follicle cells [61,73]. To determine whether Tβ4 affects the proliferation of SHF, we constructed Tβ4 overexpression and knockdown SHF-DPCs lines.…”
Section: Resultsmentioning
confidence: 99%
“…Kwack et al [60] reported that EVs derived from DPCs promote hair growth and hair regeneration by regulating the activity of follicular dermal and epidermal cells. Yan et al [61] demonstrated that EVs' microRNAs derived from DPCs mediate HFSCs' proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%